Prevalence and incidence of renal dysfunction in patients initiating Antiretroviral Therapy at a Primary Health Care Centre in Gugulethu, Cape Town : a cohort study - Kamkuemah, Monika (Department of Public Health and Family Medicine, 2015)
Includes bibliographical references.